‘Heteroaromatic Rings of the Future’: Exploration of Unconquered Chemical Space - Passador, Kevin; Thorimbert, Serge; Botuha, Candice (Synthesis, 2019)
William Pitt and co-workers have created a virtual exploratory heterocyclic library ‘VEHICLe’ containing over 200 unconquered bicyclic heteroaromatic rings, synthetically feasible with potential medicinal interest. Since the publication of the 22 ‘heteroaromatic rings of the future’ by Pitt in 2009, 15 of them have been successfully synthesized as bicyclic or polycyclic forms and evaluated for applications in both biology and material science. This short review presents the critical synthesis associated with innovative synthetic methodologies of the synthetically conquered ring scaffolds from the list of 22 with a spotlight on the scientific contribution of this fascinating article for the expansion of the chemical diversity.1 Introduction2 Heteroaromatic Rings of the Future: The Synthetic challenge?2.1 4-Pyrido[1,3]oxazin-4-one-P12.2 Pyrrolo[2,1-b][1,3]oxazin-4-one-P42.3 Furo[2,1-e]pyridazin-4(1H)-one-P52.4 Isoxazolo[3,4-c]pyridin-7-one-P62.5 5H,6H-[1,2]Thiazolo[5,4-c]pyridin-5-one-P72.6 4H,5H-Furo[3,2-b]pyridin-5-one-P82.7 1H,5H,6H-Pyrazolo[3,4-c]pyridin-5-one-P92.8 Thieno[3,4-c]pyridazine-P102.9 Pyrrolo[1,2-c][1,2,3]triazine-P112.10 Thieno[3,4-a]oxazole-P122.11 2,4-Dihydropyrrolo[3,2-c]pyrazole-P132.12 Pyrazolo[1,5-b]isoxazole-P142.13 Imidazo[1,5-c]pyrimidin-3(2H)-one-P162.14 Cyclopenta[b][1,4]oxazin-5(4H)-one-P172.15 2,3-Dihydro-2,6-naphthyridin-3-one-P183 Conclusion
Keywords: heteroaromatic rings; chemical space; medicinal chemistry; virtual exploratory heterocycle library